2020
DOI: 10.1080/21655979.2020.1816788
|View full text |Cite
|
Sign up to set email alerts
|

Implications of endophytic microbiota in Camellia sinensis : a review on current understanding and future insights

Abstract: Endophytic fungi and bacteria are the most ubiquitous and representative commensal members that have been studied so far in various higher plants. Within colonization and interaction with their host plants, endophytic microbiota are reportedly to modulate not only the host's growth but also holobiont resilience to abiotic and biotic stresses, providing a natural reservoir and a promising solution for sustainable agricultural development challenged by global climate change. Moreover, possessing the talent to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 63 publications
2
34
1
1
Order By: Relevance
“…Moreover, diversity and species richness was analyzed statistically and found to be higher in leaf than in stem segments of three medicinal plants Terminalia pallida , Rhynchosia beddomei , and Pterocarpus santalinus ( Venkateswarulu et al, 2018 ). According to these reports, the differences of endophytic communities in plant tissues are shaped by the factors such as plant species, soil type, geographic, and environmental conditions ( Xie et al, 2020 ). In this study, endophytic fungi, Clonostachys and Dactylonectria , also exhibited obvious tissue specificity, which may be caused by differences in the plant tissue microenvironment or the different physiology and chemistry of the colonized tissues ( Li et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, diversity and species richness was analyzed statistically and found to be higher in leaf than in stem segments of three medicinal plants Terminalia pallida , Rhynchosia beddomei , and Pterocarpus santalinus ( Venkateswarulu et al, 2018 ). According to these reports, the differences of endophytic communities in plant tissues are shaped by the factors such as plant species, soil type, geographic, and environmental conditions ( Xie et al, 2020 ). In this study, endophytic fungi, Clonostachys and Dactylonectria , also exhibited obvious tissue specificity, which may be caused by differences in the plant tissue microenvironment or the different physiology and chemistry of the colonized tissues ( Li et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of plant protection, fungal endophytes are considered as one of the most important sources of potential biocontrol agents because of antimicrobial, antivirus, insecticides, and the alleviation of abiotic stresses ( Park et al, 2017 ; Wen et al, 2019 ). They can reduce disease severity and pathogen biomass in the host plant via nutrient and space competition and producing various antagonistic secondary metabolites ( Rojas et al, 2020 ; Xie et al, 2020 ). These metabolites showed inhibitory activity against the spore germination of the pathogens and were also able to cause morphological changes, reduced the expression of the genes involved in mycelial growth and virulence, and induced defense-related genes ( Park et al, 2015 ; Sánchez-Fernández et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, endophytic fungi and bacteria identified in tea (Camellia sinensis) by Xie et al [85] showed an antagonistic effect on the growth of either tea plant pathogens or pathogens of other important non-medicinal crops, such as wheat and watermelon. Other findings report the antagonistic activity of microbial endophytes of C. sativa, commonly known as hemp, against three of the most threatening phytopathogens, Botrytis cinerea, Trichothecium roseum, and F. oxysporum, the etiological agents of the "gray mold" [86], the "damping off" [87], the "pink rot" [88], and Fusarium wilt [89] diseased.…”
Section: Biological Control Of Plant Pathogensmentioning
confidence: 99%
“…Earlier studies have revealed tea plants to host diverse bacterial and fungal population with distinct distribution pattern (Hu et al 2006; Nath et al 2013). The ability of endophytic fungi and bacteria in promoting plant growth through secretion indole acetic acid, gibberellin, cytokinin, siderophores, phosphate-solubilizing enzymes and ACC deaminase have also been discussed (Xie et al 2020). Microbes follow a distinct distribution pattern distribution in the plant ecosystem (Bai et al 2015; Flores-Núñez et al 2020) which may be an important plant adaptation mechanism and production of distinct bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%